2012
DOI: 10.1111/j.1468-1331.2012.03689.x
|View full text |Cite
|
Sign up to set email alerts
|

The mid‐M1 segment of the middle cerebral artery is a cutoff clot location for good outcome in intravenous thrombolysis

Abstract: The outcome of acute internal carotid artery or proximal M1 segment of the middle cerebral artery occlusion is generally poor even if treated with intravenous thrombolysis. Alternative revascularization strategies should be considered. Vascular imaging at the admission is required to guide this decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 20 publications
(34 reference statements)
3
34
1
1
Order By: Relevance
“…We also confirm a previously reported association between early recanalization and the distance of the clot from the M1 MCA origin. 20,21 Our study has limitations. We restricted our analysis of early reperfusion rates with IV tPA to baseline CTA characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also confirm a previously reported association between early recanalization and the distance of the clot from the M1 MCA origin. 20,21 Our study has limitations. We restricted our analysis of early reperfusion rates with IV tPA to baseline CTA characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For M1 MCA occlusions, we studied an additional clot characteristic by measuring the distance from the M1 MCA origin to the proximal clot interface. 20,21 Distal M1 MCA clots may be exposed to more shear stress at the proximal clot interface due to patent flow in the lenticulostriate arteries compared with proximal clots. Additionally, distal M1 clots are potentially smaller than proximal clots.…”
Section: Clot Characteristicsmentioning
confidence: 99%
“…18,27 Besides, the occlusion site and the size of thrombus also had a certain impact on the infarct volume. 15,24 In our previous study, we observed that the connections of pial recruitments to MCA could be visualized nearby the distal M1 segment while occluding proximal-MCA with single clot initially. 10 Given above factors, we chose to block M1 segment with two clots followed by ICA blockade.…”
Section: Discussionmentioning
confidence: 99%
“…15 In studies of Rink et al 2 and Christoforidis et al, 18 coils, other than thrombus, were used to generate stroke models, which called into questions about the physiological relevance of the model and risk of vasospasm or perforation of intracranial arteries. Moreover, considering that ischemic infarct was Canine stroke model with MCAO and ICA blockade Q-Q Zu et al usually caused by thrombi composed of platelets and/or fibrin in humans, the thrombin-induced clot may recapitulate an ideal stroke model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation